(untitled) (Gestionar: revista de empresa y gobierno, 2021)
This article aimed to establish the public perception of corruption in the city of Juliaca, identify those responsible, determine the degree of trust of the citizens, and know the level of expectation regarding the fight against this phenomenon. The methodology was quantitative, exploratory, and descriptive. For the result, the data were obtained through a survey. It is indicated that the leading causes of corruption are the lack of ethical values, the absence of strict laws, low salaries in the public sector, the lack of citizen surveillance in the leading institutions of the city of Juliaca, the most critical public entities. Corrupt is the national police, the judiciary, the municipalities, the regional government, and the central government. The high level of perception about corruption in public institutions has generated a loss of confidence in the transparency of institutions, authorities, and politicians.